Al Sabouni et al Reproducibility - Fenton, Isabel (Natural History Museum, 2018)
The data required to run the analyses in Al Sabouni et al "Reproducibility of species recognition in modern planktonic foraminifera and its implications for measures of community structure". Also, the images of the specimens.